2016
DOI: 10.11607/ijp.4157
|View full text |Cite
|
Sign up to set email alerts
|

Remaining Coronal Dentin and Risk of Fiber-Reinforced Composite Post-Core Restoration Failure: A Meta-analysis

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 0 publications
0
27
0
1
Order By: Relevance
“…However, in the restoration of extensively debilitated teeth, it is certain that they commonly require the use of an intracanal system with the main purpose of providing the prosthetic part with retention and stability. Generically, the use of intraradicular retainers may be classified into two categories: Cast cores and prefabricated posts [5][6] . In certain clinical situations, the selection of the type of retainer depends on various factors, among them: The degree of tooth destruction; localization of the tooth in the arch; root morphology; periodontal conditions; extension of the dental prosthesis and occlusal stress 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in the restoration of extensively debilitated teeth, it is certain that they commonly require the use of an intracanal system with the main purpose of providing the prosthetic part with retention and stability. Generically, the use of intraradicular retainers may be classified into two categories: Cast cores and prefabricated posts [5][6] . In certain clinical situations, the selection of the type of retainer depends on various factors, among them: The degree of tooth destruction; localization of the tooth in the arch; root morphology; periodontal conditions; extension of the dental prosthesis and occlusal stress 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The absence of coronal wall might increase the risk of restoration failure 30 . The study of Akkayan 2 (2004) showed no significant difference between 1 and 1.5 mm ferrules length in specimens restored with quartz fibers post and resin composite core.…”
Section: Discussionmentioning
confidence: 99%
“…A post is not a good substitute for lack of natural tooth structure within the ferrule tooth/core/post complex. The quantity of natural tooth structure within the ferrule tooth/core/post complex is more important than a post in determining whether an abutment, on which a crown is cemented, will eventually fracture away from the root 2111213141516…”
Section: The Ferrule Effectmentioning
confidence: 99%
“…However, some experiments show that the amount of natural ferrule tooth structure in an abutment is much more important than the presence of a post, in determining whether or not a ferrule/tooth/core/post complex will fracture 21112. This implies that retention of a core by strong supra-ferrule-margin natural tooth structure, containing mechanical undercuts or bonding loci to retain the core, is the most important factor in determining whether the core will be retained for a clinically useful amount of time.…”
Section: Purpose Of the Postmentioning
confidence: 99%